2017
DOI: 10.1088/1361-6463/aa97aa
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis and influence of later heat treatment on the structural evolution, optical and electrical properties of nanostructuredα-MoO3single crystals

Abstract: In the current study, α-MoO3 nanocrystals were successfully synthesized from ammonium heptamolybdate tetrahydrate using a simple hydrothermal route. The influence of calcination temperature on the structural, optical and electrical properties was systematically investigated for the MoO3 powder products. The XRD results were analyzed for these powders, revealing the formation of a mixed phase (β- and α-MoO3) at calcination temperatures ranging from 350 °C–450 °C, and hence a residual monoclinic phase still exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Although the synthesis of the m-MoO 3 phase has been carried out by many methods (spray pyrolysis, pulsed laser thin-layer deposition, molecular beam epitaxy, o-MoO 3 conversion, solution-phase reaction, etc. ), it has not been prepared hydrothermally yet in pure form, only as a part of a mixture of MoO 3 polymorphs [18]. On the other hand, it would be useful because the hydrothermal method is simple, does not use high temperatures (usually it operates only between 100 and 250 • C), results in highly crystalline, monodisperse products, and metastable phases can be also synthetized by it.…”
Section: Introductionmentioning
confidence: 99%
“…Although the synthesis of the m-MoO 3 phase has been carried out by many methods (spray pyrolysis, pulsed laser thin-layer deposition, molecular beam epitaxy, o-MoO 3 conversion, solution-phase reaction, etc. ), it has not been prepared hydrothermally yet in pure form, only as a part of a mixture of MoO 3 polymorphs [18]. On the other hand, it would be useful because the hydrothermal method is simple, does not use high temperatures (usually it operates only between 100 and 250 • C), results in highly crystalline, monodisperse products, and metastable phases can be also synthetized by it.…”
Section: Introductionmentioning
confidence: 99%
“…Where, D is the crystallite size, 𝜃 is the Bragg angle, 𝜆 is the wavelength of the X-ray radiation; 𝛽 is the full width at half maximum height (FWHM) of the diffraction peak located at 2𝜃, the constant 𝑘 is taken as 0.9 [29].…”
Section: 𝐷 = 𝑘𝜆 𝛽𝑐𝑜𝑠𝜃mentioning
confidence: 99%
“…The plots (αE) 2 vs. E for P-BFO, BC5FO, BS5FO samples are shown in figure 4 according to Tauc relation. The indirect bandgap values for BFO ceramic samples were determined from the square of the Kubelka-Munk function versus energy and extrapolation of the linear part of F 2 (R) to zero value [25]. It was found that the bandgap values for BC5FO, P-BFO, BS5FO are 2.1819 eV, 2.2011 eV, 2.2170 eV, respectively.…”
Section: Bandgap Characteristics Of Bfomentioning
confidence: 99%